Reciprocal effects of single or repeated exposure to methylphenidate or sex in adult male rats - Pallikaras, Vasilios; Mac Cionnaith, Conall E; Rosales, Vanessa C Fernandez; Arvanitogiannis, Andreas; Pfaus, James G (Psychopharmacology, 2023)
RATIONALE: Exposure to rewards can alter behavioral reactivity to them. For example, stimulants sensitize locomotor activation, whereas sexual experience sensitizes copulatory behaviors. Moreover, rewards can cross-sensitize one another. Although stimulants are known to cross-sensitize locomotor effects, the evidence for cross-sensitization between stimulants and sex is less clear. OBJECTIVES: This study determined the effects of single and repeated pre-exposure to methylphenidate (MPH) or sex on one another in adult male rats. METHODS: Cross-sensitization between MPH (5 mg/kg) and sex (30 min with sexually experienced female) was examined. Adult male rats were pre-exposed to 0, 1, or 10 trials of either sex or MPH before being exposed to the other reward. Locomotor chambers were used in MPH trials. Bilevel chambers were used in sexual trials, and sexual behaviors were video scored. RESULTS: The amount of prior sexual experience differentially influenced the ceiling of MPH-dependent sensitization; in the last drug trial, locomotion was highest in males given 1 previous sexual trial compared with 0 or 10. Compared with MPH-naive males, pre-exposure to MPH (1 and 10 trials) reduced the number of ejaculations without impacting sexual performance (intromission/mount latency and frequency). CONCLUSIONS: These findings indicate that the degree of pre-exposure to a reward can differentially affect reactivity to novel rewards. The results showed that previous findings of cross-sensitization between amphetamine and sex do not extend to MPH. However, exposure to MPH prior to sexual experience can increase the amount of sexual stimulation needed to achieve ejaculation.
Keywords: Methylphenidate; Rats; Female; Copulation; Animals; krysa rodu Rattus; ženské pohlaví; mužské pohlaví; amfetamin; Male; kopulace; Central Nervous System Stimulants; zvířata; Amphetamine; stimulanty centrálního nervového systému; methylfenidát